2010
DOI: 10.1021/cm903497h
|View full text |Cite
|
Sign up to set email alerts
|

Tuning Ferro- and Metamagnetic Transitions in Rare-Earth Cobalt Phosphides La1−xPrxCo2P2

Abstract: A family of rare-earth cobalt phosphides La 1-x Pr x Co 2 P 2 (0 e x e 1) that belong to the ThCr 2 Si 2 structure type has been prepared and characterized by structural and magnetic methods and electronic band structure calculations. All studied quaternary phases exhibit multiple magnetic transitions, leading to an observation of ferro-and metamagnetism and magnetic pole reversal. The ferromagnetic transition temperature of LaCo 2 P 2 (132 K) increases dramatically upon substitution of Pr for La and reaches 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
62
0
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 49 publications
(72 citation statements)
references
References 46 publications
9
62
0
1
Order By: Relevance
“…For instance, given the drastically different magnetic behavior of the FM LaCo 2 P 2 and AFM PrCo 2 P 2 materials, the substitution of Pr for La provides a straightforward route to modulating the exchange interactions in order to produce novel magnetic and magnetotransport properties. Indeed, our previous studies of La 1-x Pr x Co 2 P 2 showed the presence of multiple magnetic transitions in these mixed phases [14]. We found that the FM ordering temperature for the Co sublattice gradually increases with increasing Pr content (x), from 132 K for LaCo 2 P 2 to as high as 268 K for La 0.25 Pr 0.75 Co 2 P 2 .…”
Section: Introductionsupporting
confidence: 50%
See 4 more Smart Citations
“…For instance, given the drastically different magnetic behavior of the FM LaCo 2 P 2 and AFM PrCo 2 P 2 materials, the substitution of Pr for La provides a straightforward route to modulating the exchange interactions in order to produce novel magnetic and magnetotransport properties. Indeed, our previous studies of La 1-x Pr x Co 2 P 2 showed the presence of multiple magnetic transitions in these mixed phases [14]. We found that the FM ordering temperature for the Co sublattice gradually increases with increasing Pr content (x), from 132 K for LaCo 2 P 2 to as high as 268 K for La 0.25 Pr 0.75 Co 2 P 2 .…”
Section: Introductionsupporting
confidence: 50%
“…CRYSTAL STRUCTURE As shown in our earlier report, La 0.25 Pr 0.75 Co 2 P 2 has a ThCr 2 Si 2 -type structure, space group I4/mmm [14]. The structure contains layers of R atoms and [Co 2 P 2 ] slabs alternating along the c axis (Fig.…”
Section: Resultsmentioning
confidence: 80%
See 3 more Smart Citations